2017
DOI: 10.1136/jmedgenet-2016-104296
|View full text |Cite
|
Sign up to set email alerts
|

A truncating mutation in CEP55 is the likely cause of MARCH, a novel syndrome affecting neuronal mitosis

Abstract: BackgroundHydranencephaly is a congenital anomaly leading to replacement of the cerebral hemispheres with a fluid-filled cyst. The goals of this work are to describe a novel autosomal-recessive syndrome that includes hydranencephaly (multinucleated neurons, anhydramnios, renal dysplasia, cerebellar hypoplasia and hydranencephaly (MARCH)); to identify its genetic cause(s) and to provide functional insight into pathomechanism.MethodsWe used homozygosity mapping and exome sequencing to identify recessive mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 47 publications
(61 reference statements)
4
75
0
Order By: Relevance
“…During the publication process of present study, an article describing a truncating mutation in CEP55 as the likely cause of a novel syndrome MARCH was published . We do not have enough data to classify our fetuses to fulfill the criteria of MARCH syndrome, however, there are similar clinical signs between the studies.…”
Section: Discussionmentioning
confidence: 93%
“…During the publication process of present study, an article describing a truncating mutation in CEP55 as the likely cause of a novel syndrome MARCH was published . We do not have enough data to classify our fetuses to fulfill the criteria of MARCH syndrome, however, there are similar clinical signs between the studies.…”
Section: Discussionmentioning
confidence: 93%
“…We and others have shown that zebrafish can serve as robust direct models for craniofacial abnormalities observed in humans. 39,42,[48][49][50][51][52] We assessed the craniofacial patterning by measuring the angle of ceratohyal (CH) cartilage in ventral images acquired from 3 dpf larvae. We observed a significant increase of the CH angle in bptf CRISPR F0 mutants (102 versus 91 for F0 mutants versus controls; p % 0.0001, n ¼ 47-59 larvae/batch, repeated; Figure 2).…”
Section: Bptf F0 Mutants Display Abnormal Craniofacial Patterningmentioning
confidence: 99%
“…Recently, a homozygous non-sense mutation in human CEP55 has been identified in a novel perinatal lethal syndrome, MARCH syndrome, with microretrognathia and limb contractures (Frosk et al, 2017). The researchers found that the temporal cortex was disorganized and that large numbers of neurons and glial cells were multinucleated cells in MARCH patient brain tissue.…”
Section: Mutant (mentioning
confidence: 99%
“…Furthermore, CEP55 regulates the phosphoinositide 3-kinase (PI3K)/AKT pathway (Chen et al, 2009;Hwang et al, 2013), presumably leading to the promotion of tumorigenesis. Recently, a truncating mutation in human CEP55 has been identified | 643 Genes to Cells YANAGI et Al. in MARCH (multinucleated neurons, anhydramnios, renal dysplasia, cerebellar hypoplasia and hydranencephaly) syndrome (Frosk et al, 2017). It is thought that aberrant expression of CEP55 is associated with tumorigenesis; however, the developmental function of CEP55 in vertebrates is not fully understood.…”
Section: Introductionmentioning
confidence: 99%